2010
DOI: 10.1144/sp335.23
|View full text |Cite
|
Sign up to set email alerts
|

Moine Thrust zone mylonites at the Stack of Glencoul: I – microstructures, strain and influence of recrystallization on quartz crystal fabric development

Abstract: Since the early descriptions published by Callaway in 1884, the gently dipping mylonites exposed along the Moine Thrust at the Stack of Glencoul have drawn generations of geologists to the northern part of the Assynt district. These mylonites, derived from Cambrian quartzites (footwall) and Moine pelites and psammites (hanging wall), have figured prominently in: a) early research into the influence of crystal plastic deformation and recrystallization on microstructural and crystal fabric evolution; b) debates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 84 publications
3
46
0
Order By: Relevance
“…This perpendicularity seems to be reproduced by some numerical simulations (Etchecopar and Vasseur, 1987;Jessell and Lister, 1990). It has been found in many natural rocks (Carreras and Garcia-Celma, 1982;Mainprice et al, 1986), but this is not always the case at all (Law et al, 1984;Tullis, 2002;Heilbronner and Tullis, 2006;Law et al, 2010;Kilian et al, 2011).…”
Section: Introductionsupporting
confidence: 60%
“…This perpendicularity seems to be reproduced by some numerical simulations (Etchecopar and Vasseur, 1987;Jessell and Lister, 1990). It has been found in many natural rocks (Carreras and Garcia-Celma, 1982;Mainprice et al, 1986), but this is not always the case at all (Law et al, 1984;Tullis, 2002;Heilbronner and Tullis, 2006;Law et al, 2010;Kilian et al, 2011).…”
Section: Introductionsupporting
confidence: 60%
“…In this study, we revisit the classic mylonitic Cambrian quartzites in the footwall to the Moine thrust (defined by the Cambrian quartzite-Neoproterozoic Moine schist contact; Peach et al, 1907;Christie, 1963;Law et al, 2010) exposed at the Stack of Glencoul in the Assynt region of northwest Scotland (Fig. 1) in order to measure molecular water contents as a function of structural level, from 70 m below the principal thrust surface to within 5 mm of the thrust contact.…”
Section: Water Weakeningmentioning
confidence: 99%
“…Kruhl [] suggested that the opening angles in plane strain may be used as a deformation thermometer, whereas Law et al . [] provided the caveat that the degree of dynamic recrystallization and non‐plane strain deformation probably also affect the opening angle. Opening angles for our samples that featured [c]‐axis crossed‐girdles (and their estimated uncertainty) are presented in Table B and Figure , and are also depicted on the complete set of [c]‐axis pole figures (Appendix C).…”
Section: Other Fabric Changes With Increasing Structural Depth Into Tmentioning
confidence: 99%
“…[33] The crossed-girdle opening angle of quartz c-axis LPOs may be a function of deformation temperature, hydrolytic weakening, or strain rate [Tullis et al, 1973;Lister & Hobbs, 1980;Kruhl, 1998;Law et al, 2004]. Kruhl [1998] suggested that the opening angles in plane strain may be used as a deformation thermometer, whereas Law et al [2010] provided the caveat that the degree of dynamic recrystallization and non-plane strain deformation probably also affect the opening angle. Opening angles for our samples that estimated uncertainty) are presented in Table B and Figure 10, and are also depicted on the complete set of [c]-axis pole figures (Appendix C).…”
Section: Quartz Lpo Opening Anglesmentioning
confidence: 99%